The Broadband Albedo of Snow - Kokhanovsky, Alexander A. (Frontiers in Environmental Science, 2021)
The asymptotic radiative transfer theory is used to derive the analytical approximation for the broadband albedo of pure and polluted snow surfaces. The technique for the determination of the effective snow grain size and also the snow specific surface area from the shortwave broadband albedo measurements is proposed.